PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 3 BATUSANGKAR - Aviva, Fitria; Thahar, Harris Effendi; Hafrison, Mohammad (Universitas Negeri Padang, 2016)
ABSTRACT The purpose of the research is to description the effects of the problem based learning model in the skill of writing the news for students at VIII grade SMP Negeri 3 Batusangkar. The method used is the experiment method. Based on the results of data analysis it was concluded the following three points. First, the skills of writingthe news before use of the problem based learning model students in class VIII was on qualifications more than enough with the average value of 68,41. Second, the skill of writing the news after use of the problem based learning model students in class VIII was on qualification Good with the average value of 77,94. Third, based on the results of uji-t, it was concluded that there is a effects of problem based learning model in the skills of writing the news for students at VIII grade SMP Negeri 3 Batusangkar because the value is tarrmatic>ttable (2,87>1,68). Kata kunci: pengaruh, model problem based learning,menulis,berita